Association between allergic rhinitis and atopic bronchial asthma: a study of 125 cases (Journal of Dhaka Medical College, 2015)
Background: The aim of the present study was to see the prevalence of allergic comorbidities among the countrys population and to increase impression of cost savings in the management of allergic comorbidities. Methods: The study was done in the ENT outpatient department (OPD) of Dhaka Medical College Hospital, Dhaka, from January 2011 to January 2012 and 125 patients with allergic rhinitis with or without other allergies were selected over the period of study. Results: Among the patients affected by allergic rhinitis along with other allergies 64% patients were male and 36% were female. Maximum patients for both male and female were of the age group of 21-30 years (46%). From the occupational point of view, students were mostly affected (34% of the total patients). Maximum patients were suffering from allergic rhinitis along with atopic asthma and allergic conjunctivitis (22%) and atopic asthma patients were about 55% of the total patients of allergic rhinitis. Maximum patients of atopic asthma were of the age group of 21-30 years (48%) for both male and female. 100% asthmatic patients were suffering from chest tightness, 90% from cough, 87% from respiratory distress, 22% from wheeze 85% patients got positive stair test. 82% of the total patients of allergic rhinitis got eosinophilia, 68% got hyperimmunoglobulinemia IgE and 25% got eosinophil in their nasal smear. 87% patients with atopic asthma got eosinophilia, 83% got hyperimmunoglobulinemia IgE and 45% got eosinophil in their nasal smear- maximum patients (17%) got the total circulatory eosinophil level from 901 to 1000 per cubic milimeter and maximum patients (32%) got the IgE level from 100-300 per international unit. A good number of patients with atopic asthma selected randomly underwent spirometry test after having proper and adequate treatment of allergic rhinitis for few months along with bronchodilator for few weeks and they got no pulmonary obstruction. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21524 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 144-150